Banquets, rations et offrandes alimentaires au Proche-Orient ancien - Bonneterre, Daniel, 1956- (Oxford, UK)
xvi, 387 sayfa
Keywords: “Banquets, Rations et Offrandes alimentaires au Proche-Orient ancien investigates the essential question of food consumption in the ancient Near East, in particular between the 4th and 1st millennium BC. Thanks to archaeological discoveries and to abundant textual documentation, historians are well equipped to reconstruct the food supply of the cities of Mesopotamia and have a better idea of the variety of products available, a far greater range than might be imagined. The analysis of the treatment of ingredients also reveals techniques unsuspected in pre-industrial times. The codification of culinary recipes developed for the use of temples also reflects a high stage of development. Religious rituals were based on a structured code of food consumption, of which prohibitions and taboos are only one facet. The book presents some aspects of everyday life in a new light. First and foremost, the banquet is seen as a critical institution in shaping urban behaviour. The representation of feasts and banquets in temples and palaces are classic themes of ancient art and literature. Understanding the importance of the meal as a rite of social cohesion, furthermore, allows us to better envision events that would unfold centuries later” --